Public Sentiment Analysis on the Launch of Danantara Using Support Vector Machine (SVM) Algorithm Based on Data from the X Social Media Platform - Fernando, Ziagy Aji; Rumini, Rumini; Susanto, Tri (Journal of Artificial Intelligence and Software Engineering, 2025)
Efficient management of national wealth and resources is key to realizing the welfare of the Indonesian people. The Daya Anagata Nusantara Investment Management Agency (BPI Danantara) was established as a strategic institution aimed at optimizing government investments to drive national economic growth. The launch of the Danantara Project has sparked various public responses, particularly on the social media platform X, which has become a space for citizens to express their opinions on government policies. This study aims to analyze public sentiment toward the Danantara Project using the Support Vector Machine (SVM) algorithm. By processing 3,152 posts from the period of February 24 to April 4, 2025, the SVM model demonstrated strong performance with an accuracy of 87%. The research findings indicate that positive sentiment is quantitatively more dominant, reflecting public expectations of national investment progress and strategic project management. However, negative sentiment is also quite significant, highlighting issues of corruption, lack of transparency, and potential project failure.